QARAQALPAQSTAN PAYDALÍ QAZÍLMA KÁNLERIN GEOLOGIYALÍQ IZERTLEW TARIYXÍNAN - Ajieva, M.; Bekimbetova, G. (SCIENCE and SOCIETY, 2024)
This article contains information about the history of the study and discovery of natural minerals in the Republic of Karakalpakstan from the 10th year BC to the present day. It also provides information on the use of minerals in the national economy.